SOEP-IS 2016 - PGEN: Person-related status and generated variables - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Variables in the file pgen documented here are generated mostly from the answers in the personal questionnaire. There is one row for each wave (syear) a person (pid) participated in the survey.
Keywords: 330